An excellent gain flatness 3.0-7.0 GHz CMOS PA for UWB applications - Sohiful Anuar, Zainol Murad; Pokharel, R. K.; Galal, A. I. A.; Sapawi, R.; Kanaya, H.; Yoshida, K. (Institute of Electrical and Elctronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/